Physicomechanical Properties of Nanobiocomposite Composed of Polylactic Acid and Biogenic Nano Hydroxyapatite - Bano, Nazia; Basri, Hatijah; Jikan, Suzi Salwah; Syed Abu Bakar, Sharifah Adzila; Badarulzaman, Nur Azam (International Journal of Integrated Engineering, 2019)
The main function of bone repair is to adjust the fractured bone in order to allow fast back healing and complete functionality of the injured bone part. Metallic implants have many problems such as stress shield, palpation and temperature sensitivity etc. Consequently, biodegradable bioactive composite gained interest as they avoid elimination and increase bone renovation due to lack of stress shielding effect. In the current paper, nanobiocomposite consisting of polylactic acid (biodegradable) (PLA) and nano hydroxyapatite (bioactive) (n-HAP) extracted from bovine bone was fabricated through melt mixing and injection moulding technique for biomedical application. Partially biogenic n-HAP was obtained from bovine bone by hydrothermal and calcination processes. Physicomechanical properties of neat PLA and PLA/n-HAP nanobiocomposite are evaluated using universal testing machine (UTM) and scanning electron microscopy (SEM). The results revealed that the higher n-HAP loading (1-5 wt%) in PLA matrix, the lower the tensile strength of nanobiocomposite. PLA/n-HAP with 1 wt% loading exhibits tensile strength potential for bone implant application and can be promising biomedical materials for orthopedic applications.